Exploratory factors structural Internet expectancy - GarciÂa Lirios, Cruz (ACEND Foundation, 2021)
Studies on the consumption of information technologies, electronic devices and digital networks have shown that expectations are explanatory variables of processes of acceptance, adoption and intensive use that would be linked to anxiety and addiction, as well as to processes of aggression such as stalking, buying or infidelity. In the case of the Internet and electronic networks such as Facebook, Twitter, Instagram, SnapChat, Periscope, YouTube or WhatsApp, there have been trends towards violence that can trigger and suicidal ideation. However, the measurement of the sociocultural and sociocognitive determinants of intensive use have not established integral models that explain the structure of relations between the variables. Therefore, the present work was proposed to validate an instrument that measures the phenomenon, considering the exposure or the intensive use of electronic networks. The factors that determine the intention of use in a factor structure that explained 63% of the total variance were confirmed, although the design limits the findings to the research scenario, suggesting the inclusion of another factor related to the behavior.